Korelasi Tafsir Maqasidi Dalam Konteks Childfree: Perspektif Agama, Social, dan Budaya - Kayza Safitri Nst; Katimin (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
The concept of childfree centers on the freedom to pursue personal life goals without the responsibility of raising children. Parenthood plays a significant role in determining one’s quality of life. This study explores the correlation between the interpretation of Maqasid al-Shariah and the childfree phenomenon from religious, social, and cultural perspectives. The research delves into the understanding of childfree through these lenses and employs the Maqasid al-Shariah interpretive approach for analysis. The methodology used in this research is qualitative, relying on a literature review approach (library research). The childfree phenomenon is often linked to the shift in modern values that emphasize individual autonomy, women’s rights over their own bodies, and economic considerations. In contemporary society, especially in urban areas, the decision to remain childfree is frequently viewed as part of a lifestyle that prioritizes career and personal achievements. Surah An-Nahl, verse 72, states that Allah created humans in pairs, from whom offspring are born. While this verse is pivotal, a maqasidi interpretation suggests that the decision to remain childfree should be considered within the broader context of individual well-being and circumstances